Seismic Protection of Cabinet Stored Cultural Relics with Silicone Dampers. (15th May 2018) - Ning, Xiaoqing; Dai, Junwu; Bai, Wen; Yang, Yongqiang; Zhang, Lulu
Abstract : Cultural relics are precious properties of all humankind, the damage of which is nonresilient. In previous earthquakes, stored cultural relics have shown poor seismic performance, so effective seismic methods are urgently needed. However, due to various restrictions, traditional damping methods are not suitable for the cultural relics stored in the Palace Museum. An efficient damping method, composed of silicone damper and connecting elements, is proposed to protect these stored cultural relics. This novel damping device is very convenient to install and no change or move for the original structures is needed. It is suitable for various kinds of new and existing relic cabinets. In order to validate the effectiveness of this novel damping method, both numerical simulation and shaking table tests are carried out. Results show that this method can effectively enhance the seismic performance of relic cabinet itself and the internal cultural relics. Relic cabinets with damping devices deform significantly less than noncontrol cabinets while the inside relics also have less sliding or overturning. Overall, a damping method, designed for seismic protection of cabinet stored cultural relics, is proposed and its effectiveness has been successfully demonstrated.